Non-idiopathic-intracranial hypertension: A case report - Anand, Rajiv; Maini, Deepinder Kaur; Wani, Tanzeel Ahmad; Rehani, Varun (Indian Journal of Case Reports, 2024)
Idiopathic intracranial hypertension (IIH) is a condition characterized by headache, visual obscuration, and pulsatile tinnitus caused due to raised intracranial pressures without any underlying pathology of brain parenchyma or its structure. The diagnosis of IIH can be reconsidered especially when there are no risk factors associated during presentation. This is a case report of a 27-year-old young girl with normal body mass index (BMI), who presented with persistent headache and tinnitus. Fundus examination revealed papilledema, with magnetic resonance imaging of the brain and orbit showing flattening of the posterior sclera and tortuous optic nerve. A patient with a normal BMI should always raise suspicion for secondary causes of IIH. She was using topical retinol gel for acne which is available easily over the counter. It is therefore important to raise awareness for such agents. Recognizing and discontinuation of these offending agents can prevent the progression and reversal of IIH symptoms.